Transcriptome analysis of perirenal fat from Spanish Assaf suckling lamb carcasses showing different levels of kidney knob and channel fat - Alonso-García, María; Suárez-Vega, Aroa; Fonseca, Pablo A. S.; Marina, Héctor; Pelayo, Rocío; Mateo, Javier; Arranz, Juan-José; Gutiérrez-Gil, Beatriz (Frontiers in Veterinary Science, 2023)
Suckling lamb meat is highly appreciated in European Mediterranean countries because of its mild flavour and soft texture. In suckling lamb carcasses, perirenal and pelvic fat depots account for a large fraction of carcass fat accumulation, and their proportions are used as an indicator of carcass quality. This study aimed to characterize the genetic mechanisms that regulate fat deposition in suckling lambs by evaluating the transcriptomic differences between Spanish Assaf lambs with significantly different proportions of kidney knob and channel fat (KKCF) depots in their carcasses (4 High-KKCF lambs vs. 4 Low-KKCF lambs). The analysed fat tissue showed overall dominant expression of white adipose tissue gene markers, although due to the young age of the animals (17-36 days), the expression of some brown adipose tissue gene markers (e.g., UCP1, CIDEA) was still identified. The transcriptomic comparison between the High-KKCF and Low-KKCF groups revealed a total of 80 differentially expressed genes (DEGs). The enrichment analysis of the 49 DEGs with increased expression levels in the Low-KKCF lambs identified significant terms linked to the biosynthesis of lipids and thermogenesis, which may be related to the higher expression of the UCP1 gene in this group. In contrast, the enrichment analysis of the 31 DEGs with increased expression in the High-KKCF lambs highlighted angiogenesis as a key biological process supported by the higher expression of some genes, such as VEGF-A and THBS1, which encode a major angiogenic factor and a large adhesive extracellular matrix glycoprotein, respectively. The increased expression of sestrins, which are negative regulators of the mTOR complex, suggests that the preadipocyte differentiation stage is being inhibited in the High-KKCF group in favour of adipose tissue expansion, in which vasculogenesis is an essential process. All of these results suggest that the fat depots of the High-KKCF animals are in a later stage of development than those of the Low-KKCF lambs. Further genomic studies based on larger sample sizes and complementary analyses, such as the identification of polymorphisms in the DEGs, should be designed to confirm these results and achieve a deeper understanding of the genetic mechanisms underlying fat deposition in suckling lambs.